Domain specificity of creativity - Baer, John, 1948- (Explorations in creativity research., 2016)
Recent research findings have challenged the idea that creativity is domain-general. Domain Specificity of Creativity brings together the research information on domain specificity in creativity -- both the research that supports it and answers to research arguments that might seem to challenge it. The implications for domain specificity affect how we move forward with theories of creativity, testing for creativity, and teaching for creativity. The book outlines what these changes are and how creativity research and applications of that research will change in light of these new findings.